Nad1 gene analysis of Echinococcus granulosus from sheep in Aqrah city, Iraq - R.N. Hamoo; nashaat Mustafa; S.A. Abdulraheem (Iraqi Journal of Veterinary Sciences, 2019)
Echinococcus granulosus (E. granulosus) is a dog tapeworm cestoda; it is larval stage responsible to cystic echinococcosis, one of the most common and dangerous worldwide zoonotic parasitic disease. The aim of this study was the molecular identification of the local strain of E. granulosus isolated from sheep liver slaughtered in the principal abattoir of Aqrah city, Northern of Iraq during Jun-Nov. 2017. In this study, 37 sheep liver infected by E. granulosus, 12 of high DNA purity fertile (have protoscolices) cyst of them were considered. A molecular study conducted on the mitochondrial NADH dehydrogenase 1 (nad1) gene. Results demonstrated that E. granulosus isolates were sheep strain (G1) genotype, with fascinating highly corresponding 95% and 96% to global isolates, particularly to north African and Mediterranean countries, by employing phylogenetic tree analysis. So, the isolates of our project were deposited in Genbank (accession No. MG792129). This study findings provide that the local isolates of E. granulosus from sheep liver in Aqrah city, Northern of Iraq are loyally equivalent to global strains and isolates, in addition, nad1 gene considers a perfect biomarker in a molecular identification and phylogenetic study of this parasite.